O estudo do Instituto Fernando Henrique Cardoso na perspectiva da teoria arquivística pós-custodial - Graciano, Maítha Elena Tosta [UNESP] (2015)
This research analyzed and discussed the organization of information guarded by the Institute Fernando Henrique Cardoso (iFHC) as proposed by the post-custodial paradigm of the analysis lines of Contemporary Archives. This research is justified because in order to be allowed access to any collection, it is necessary to be used in the documentary mass prerogatives as techniques and methods of organizing information respecting mainly the principles of provenance, the original order, the organic nature and also the context and functions established at the time of production of documentation and throughout the term and procedure in current state. The post-custodial theory in just puts this strong link between the document and the information, from production to user-access. This research is characterized as qualitative descriptive method which is the case study with simple systematic observation unstructured. This research will present a paradigm shift in development in today's Archives and the Information Science, and how these ideas influenced the organization of iFHC the acquis and the different possibilities offered by the institution for access to information in its collection. It was found that, often, the organization and the understanding given to personal and private archives, in contemporary times, is that they are documents of museum or collection biblioteconômico character and not a characteristic and organic set of documents relevant to file. The Instituto Fernando Henrique Cardoso documentation covers the period in which its founder was Minister and President of the Republic of Brazil (1994-2002), the collection also consists of personal documents, and documents produced from its activities as an intellectual, sociologist, university, political and writing teacher, and Fernando Henrique Cardoso very active in some of them. The collection includes not only documents and texts, letters, books and notes, but also photographs, ...